Efek Impostor Syndrome terhadap Kecemasan Akademik Mahasiswa Baru Universitas Negeri Padang - Ahmad Abrar; Devi Rusli (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The transition from secondary to higher education is often a psychologically challenging period for new university students, one of which is academic anxiety—defined as feelings of worry related to academic demands and expectations. One internal factor influencing this condition is impostor syndrome, a psychological state where individuals feel undeserving of their achievements and believe that their success is merely due to luck or external factors. This study aims to examine the effect of impostor syndrome on academic anxiety among first-year students at Universitas Negeri Padang, class of 2024. A quantitative approach was applied using a survey method. The population consisted of undergraduate students (S1), with a sample of 385 participants selected through purposive sampling. The instruments used were the State-Trait Anxiety Inventory (STAI) modified from Batubara (2022) to measure academic anxiety, and the Clance Impostor Phenomenon Scale (CIPS) from Pikoli (2023) to assess impostor syndrome. Data were collected via Google Forms and direct distribution to respondents. Data analysis was conducted using simple regression with the aid of IBM SPSS version 25. The results showed a significance value of 0.000 < 0.05, with a coefficient of 0.854 and an R Square of 0.295. These findings indicate that impostor syndrome has a positive effect on academic anxiety by 29.5%. Therefore, the higher the impostor syndrome experienced by students, the higher their level of academic anxiety.